Maritime work material based on geopolymerization technology and preparation method thereof
Through grinding and moving slag and flour ash, preparation of ground polymer and ground polymerization solution, combined with basalt fiber, solving the problem of poor corrosion performance of existing sea industry materials in the marine environment, and realizing the resistance of sea industry materials. Interest improvement and stability improvement, and reduced costs.
Patent Information
- Application Number
- CN202411265026.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-10
- Publication Date
- 2025-01-21
AI Technical Summary
In the marine environment, existing marine materials have anti-chlorine ions, poor sulfate corrosion resistance, carbonization resistance and erosion resistance. The materials are complex and costly, making it difficult to achieve economical, efficient, durable and highly applicable sea-based materials. Materials.
Through grinding and moving slag and flour ash, preparation of ground polymers, and optimizing the distribution ratio of sea industrial materials, use sodium silicate and sodium hydroxide solution to prepare ground polymerization solution, combined with basalt fiber to prepare high pressure resistance strength , Stability of the sea industry materials.
The pressure resistance of sea industry materials is improved, the stability improves, the cost is reduced, the cost of high -salt is resistant to high -salt seawater can effectively dispose of hazardous wastes such as waste alkali solution and realize resource utilization.
Smart Images

Figure CN119330642A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of new environmentally friendly functional materials and relates to a marine engineering material based on geopolymerization technology and a preparation method thereof. Background Art
[0002] Marine engineering materials refer to various artificial synthetic materials used in marine engineering construction that are resistant to corrosion, wear, high pressure and impact, and can be used stably and for a long time in the marine environment. They usually include steel, concrete, fiberglass composite materials, etc. In particular, in the construction of marine ranches, cement / concrete is widely used as a marine engineering material, mainly used as a matrix material for the attachment, nesting and reproduction of marine organisms. However, cement usually has poor resistance to chloride ion and sulfate erosion, poor carbonization resistance and poor scouring resistance. It is eroded by sea breeze, waves and seawater, causing steel bar corrosion, and the cement surface to peel off, crack and collapse.
[0003] In recent years, geopolymer-based materials have also been studied for use in marine engineering materials. They utilize industrial solid waste and the special three-dimensional network structure of geopolymers. While ensuring that marine engineering geopolymers have good mechanical properties, they can also improve their durability. It is a new type of material with great application potential.
[0004] At present, there are some relevant research reports on offshore geopolymer materials at home and abroad. For example, a offshore geopolymer material and its preparation method (CN202211332004.0) reports that the geopolymer cementitious material is composed of slag powder, ground basalt powder, kaolin, light-burned magnesium powder, anhydrite, sea sand, fly ash microbeads, basalt chopped fibers, microfibers, water glass, alkaline activator, composite rust inhibitor, water reducer, etc. It has the characteristics of low carbon, environmental protection, high strength, good toughness, etc., but the material composition is complex and the cost is relatively high, and practical application will face challenges.
[0005] Therefore, seeking an economical, efficient, durable and highly applicable geopolymer marine engineering material is of great significance for the research and development and application of new marine materials. Summary of the invention
[0006] The present invention aims to provide a marine engineering material based on geopolymerization technology and a preparation method thereof, which optimizes the composition ratio of the marine engineering material through high-energy activation of the geopolymerization agent components, and obtains a marine engineering material with high compressive strength and good stability. The raw material types and preparation process are simple, no additional multiple additives are required, the cost is low, the material is resistant to high-salinity seawater corrosion, and the stability is strong. The solid waste-based raw materials used have a high mixing ratio. At the same time, hazardous wastes such as waste alkali liquor can be disposed of to realize the resource utilization of hazardous wastes.
[0007] In a first aspect, the present invention provides a method for preparing marine engineering materials based on geopolymerization technology, comprising the following steps:
[0008] Preparation of geopolymerization agent: grinding and activating slag and fly ash to obtain geopolymerization agent, wherein the mass ratio of slag to fly ash is 1:2-4;
[0009] Preparation of geopolymer solution: after mixing sodium silicate solution and sodium hydroxide solution, adding solvent and mixing, to obtain geopolymer solution;
[0010] Preparation of marine engineering materials: Mix the geopolymer and aggregate, then add a mixture of geopolymer liquid and water, stir evenly, pour into a mold, vibrate and compact, cure and demould, and obtain the marine engineering materials.
[0011] In some embodiments, the geopolymeric fluid has a modulus of 1.0-1.4; the geopolymeric fluid has a basicity of 6%-8%;
[0012] Preferably, the modulus of the geopolymeric liquid is 1.2-1.4; the alkalinity of the geopolymeric liquid is 6%-7%.
[0013] In some embodiments, the aggregate includes coarse aggregate and fine aggregate;
[0014] Preferably, the coarse aggregate is at least one of pebbles and crushed stones, and the fine aggregate is sand;
[0015] Preferably, the weight ratio of the coarse aggregate to the fine aggregate is 25%-40%;
[0016] Preferably, the weight ratio of the coarse aggregate to the fine aggregate is 30%-35%.
[0017] In some embodiments, the geopolymeric agent has a specific surface area greater than 400 m 2 / kg.
[0018] In some embodiments, the mass ratio of the aggregate to the geopolymeric agent is 2-5:1;
[0019] Preferably, the mass ratio of the aggregate to the geopolymer is 3-5:1.
[0020] In some embodiments, in the step of preparing the marine engineering material, the mass ratio of water to geopolymerizing agent is 0.3-0.45;
[0021] Preferably, the mass ratio of water to geopolymerizing agent is 0.35-0.4.
[0022] In some embodiments, the solvent includes at least one of purified water, distilled water, tap water, recycled water, groundwater, seawater, and a waste lye intermediate;
[0023] Preferably, the waste alkali solution intermediate is obtained by filtering, evaporating and adjusting the alkalinity of the waste alkali solution in sequence.
[0024] In some embodiments, the preparation of the marine engineering material further comprises adding basalt fiber and mixing, and then pouring into a mold and vibrating to compact it;
[0025] Preferably, the amount of basalt fiber added is 0.3%-1.5% of the marine engineering material;
[0026] Preferably, the basalt fiber is added in an amount of 0.5%-1.5% of the marine engineering material.
[0027] In a second aspect of the present invention, there is provided a marine engineering material, which is prepared by any one of the preparation methods described above, and the compressive strength of the marine engineering material is 45-50 MPa;
[0028] Preferably, the compressive strength of the marine engineering material is 47 MPa.
[0029] In some embodiments, the marine engineering material comprises the following components in parts by weight: 240-400 parts of geopolymerizing agent, 1000-1400 parts of aggregate, 140-160 parts of geopolymerizing liquid, and 50-100 parts of water;
[0030] Preferably, the aggregate comprises 750-800 parts of coarse aggregate and 400-450 parts of fine aggregate;
[0031] Preferably, the geopolymerizing agent comprises the following components in parts by weight: 85-95 parts of slag, 205-215 parts of fly ash,
[0032] Preferably, the geopolymeric liquid comprises the following components in parts by weight: 60-65 parts of sodium silicate, 15-20 parts of sodium hydroxide, and 65-70 parts of solvent.
[0033] In summary, the present application includes at least one of the following beneficial technical effects: by grinding and activating a specific ratio of slag and fly ash, the obtained marine engineering material has high compressive strength and good stability. The raw material types and preparation process of the preparation process are simple, no additional multiple additives are required, the cost is low, the material is resistant to high-salinity seawater corrosion, and the stability is strong. The solid waste-based raw materials used have a high mixing ratio, and hazardous wastes such as waste alkali liquor can be disposed of, realizing the resource utilization of hazardous wastes. BRIEF DESCRIPTION OF THE DRAWINGS
[0034] Figure 1 This is a process flow chart of the marine engineering material prepared by the present invention;
[0035] Figure 2 A sample diagram of marine engineering materials prepared by the present invention;
[0036] Figure 3 This is a state diagram of the durability test of the marine engineering material prepared in Example 1 of the present invention;
[0037] Figure 4 This is the state diagram of the durability test of standard C30 concrete;
[0038] Figure 5 This is a SEM image of the fly ash after activation treatment of the present invention. DETAILED DESCRIPTION
[0039] The technical solution of the present invention is further described below by specific embodiments, which do not limit the protection scope of the present invention. Some non-essential modifications and adjustments made by others based on the concept of the present invention still fall within the protection scope of the present invention.
[0040] Geopolymer fluid modulus: the molar ratio of silicon oxide to sodium oxide in geopolymer fluid; the modulus in sodium silicate is n=SiO2 / Na2O (molar ratio). The modulus shows the composition of sodium silicate and is an important parameter of sodium silicate, generally between 2.2-3.5.
[0041] Alkalinity: the mass ratio of sodium oxide to geopolymer;
[0042] Water-cement ratio: the mass ratio of all water to geopolymer used in the preparation of marine materials;
[0043] Aggregate-cement ratio: the weight ratio of aggregate to geopolymer in marine materials;
[0044] Sand ratio: the mass ratio of sand (fine aggregate) to aggregate (the sum of coarse aggregate and fine aggregate);
[0045] Example 1
[0046] A method for preparing marine engineering materials based on geopolymerization technology comprises the following steps:
[0047] Preparation of geopolymer: 90 kg of slag and 210 kg of fly ash were activated by high-speed grinding in a ball mill at 500 r / min to obtain a specific surface area greater than 400 m 2 / kg of powdered geopolymerizing agent;
[0048] Preparation of geopolymer solution: 62.17 kg of sodium silicate solution (50 degrees Baume) and 15.22 kg of sodium hydroxide powder were mixed, and then 67.7 kg of pure water was added to obtain a geopolymer solution with a modulus of 1 and a basicity of 6%;
[0049] Preparation of marine engineering materials: 300 kg of geopolymer, 780 kg of crushed stone as coarse aggregate, and 420 kg of sand as fine aggregate are put into a mixer and stirred for 30 seconds to mix evenly, then a mixture of 150 kg of geopolymer liquid and 60 kg of tap water and 17 kg of basalt fiber are added, and stirring is continued for 90-120 seconds to mix evenly. The water-cement ratio is 0.35, the sand rate is 35%, and then poured into a mold, placed on a vibration table or vibrated with a vibrating rod to make it dense, and the opening is sealed with a plastic mold (to avoid rapid water loss and cracking during molding), and the cast mold is demolded after curing in a 60°C curing room for 24 hours, and then the formed solidified body is cured at room temperature to an age of 28 days to obtain a marine engineering material.
[0050] In this embodiment, the selection of coarse aggregate meets the requirements of "Stone for Coarse Aggregate" GB / T14684-2011, "Pebble for Coarse Aggregate" GB / T14685-2011, "Crushed Stone for Coarse Aggregate" GB / T25177-2010, "Crushed Stone for Coarse Aggregate" GB / T25178-2010, "Crushed Stone Blocks for Coarse Aggregate" GB / T25179-2010, and "Crushed Gravel for Coarse Aggregate" GB / T25180-2010; the selection of fine aggregate shall meet the requirements of "Sand for Construction" GB / T 14684-2011.
[0051] Example 2
[0052] A method for preparing marine engineering materials based on geopolymerization technology comprises the following steps:
[0053] Preparation of geopolymer: 90 kg of slag and 210 kg of fly ash were activated by ball mill at 500 r / min to obtain a specific surface area greater than 400 m 2 / kg of powdered geopolymerizing agent;
[0054] Preparation of geopolymer solution: 62.17 kg of sodium silicate solution (50 degrees Baume) and 15.22 kg of sodium hydroxide powder were mixed, and 67.7 kg of waste alkali solution intermediate was added and mixed to obtain a geopolymer solution with a modulus of 1 and a basicity of 6%;
[0055] In this embodiment, the waste alkali liquid intermediate is a clear and transparent liquid obtained by filtering the waste alkali liquid through a 40 μm pore size filter membrane and evaporating it at a vacuum degree of 50-60° and 0.9 MPa.
[0056] Preparation of marine engineering materials: 300 kg of geopolymer, 780 kg of crushed stone as coarse aggregate, and 420 kg of sand as fine aggregate are put into a mixer and stirred for 30 seconds to mix evenly, then a mixture of 150 kg of geopolymer liquid and 60 kg of water and 17 kg of basalt fiber are added, and stirring is continued for 90-120 seconds to mix evenly. The water-cement ratio is 0.35, the sand ratio is 35%, and then poured into a mold, placed on a vibration table or vibrated with a vibrating rod to make it dense, and the opening is sealed with a plastic mold (to avoid rapid moisture loss and cracking during molding), and the cast mold is demolded after curing in a 60°C curing room for 24 hours, and then the formed solidified body is cured at room temperature to an age of 28 days to obtain a marine engineering material.
[0057] In this embodiment, the selection of coarse aggregate meets the requirements of "Stone for Coarse Aggregate" GB / T14684-2011, "Pebble for Coarse Aggregate" GB / T14685-2011, "Crushed Stone for Coarse Aggregate" GB / T25177-2010, "Crushed Stone for Coarse Aggregate" GB / T25178-2010, "Crushed Stone Blocks for Coarse Aggregate" GB / T25179-2010, and "Crushed Gravel for Coarse Aggregate" GB / T25180-2010; the selection of fine aggregate shall meet the requirements of "Sand for Construction" GB / T 14684-2011.
[0058] Effect example
[0059] 1. At present, standard C30 concrete is mainly used as marine engineering material. Therefore, a durability test is conducted on the geopolymer marine engineering material prepared in Example 1 and the standard C30 concrete. The specific experimental method is as follows:
[0060] (1) The sulfate resistance test was carried out in accordance with the national standard GB / T50082-2009 "Standard for Test Methods of Long-term Performance and Durability of Ordinary Concrete". The sulfate resistance of geopolymer marine engineering materials and C30 concrete was determined using the dry-wet cycle test method. The results are as follows:
[0061] Table 1 Comparison of sulfate corrosion resistance
[0062]
[0063]
[0064] (2) According to the national standard GB / T50082-2009, the chloride ion penetration test was carried out, and the chloride ion penetration resistance of geopolymer marine engineering materials and C30 concrete was determined by the electric flux test method. The results are as follows:
[0065] Table 2 Comparison of chloride ion penetration resistance
[0066] Serial number Experimental samples Electric flux 1 Geopolymer Marine Engineering Materials 163.85C 2 C30 Concrete 1545C
[0067] The relationship between electrical flux and chloride ion permeability is shown in the following table:
[0068] Table 3 Relationship between electric flux and chloride ion permeability
[0069]
[0070] It can be seen from the above experiments that the geopolymeric marine engineering material prepared by the present invention is superior to C30 concrete in terms of resistance to sulfate corrosion and resistance to chloride ion permeability, and can be used as a marine engineering material.
[0071] 2. The geopolymer marine engineering material prepared in Example 1 was subjected to a compatibility test and compared with the standard C30 concrete. The sample was immersed in seawater. The seawater was replaced every three days during the experiment. The surface and internal leaching pH values of the sample were measured according to the "Glass Electrode Method for Determination of pH Value of Water Quality" GB6920-86 and the "Atomic Absorption Spectrophotometry" GB7475-87 to characterize the compatibility with the ocean (the pH value of the experimental seawater was 7.67). The results are as follows:
[0072] Table 4 pH value measurement results
[0073]
[0074] The experimental results show that the surface pH value of geopolymer marine engineering materials is almost close to the pH value of seawater after being immersed in seawater for 60 days, and remains consistent with the pH value of seawater after being immersed in seawater for 90 days. The internal pH value gradually approaches the pH value of seawater after being immersed in seawater for 90 days. It can be concluded that geopolymer marine engineering materials are slightly better than C30 concrete in terms of marine compatibility.
[0075] Comparative Example 1 explores different Slag and fly ash addition ratio , the impact on the results
[0076] A method for preparing marine engineering materials based on geopolymerization technology, which differs from Example 1 in that, in the step of preparing the geopolymerizing agent, slag and fly ash are mixed according to the ratio shown in Table 5 below to obtain the geopolymerizing agent, and in the step of preparing the geopolymerizing liquid, sodium hydroxide, sodium silicate and water are mixed according to the ratio shown in Table 5 below to obtain the geopolymerizing liquid.
[0077] Table 5 Different slag and fly ash addition ratios
[0078] Experimental Group Slag kg Fly ash kg Sodium hydroxide kg Sodium silicate kg Water kg A1 20 80 5.42 27.69 18.39 A2 30 70 5.42 27.69 18.39 A3 40 60 5.42 27.69 18.39 A4 50 50 5.42 27.69 18.39 A5 60 40 5.42 27.69 18.39 A6 70 30 5.42 27.69 18.39 A7 80 20 5.42 27.69 18.39
[0079] The marine engineering materials prepared in the experimental group A1-7 were subjected to surface observation and compressive strength testing. The specific testing method was in accordance with the Technical Standard for Field Testing of Concrete Structures GB / T50784-2013.
[0080] The results are as follows:
[0081] Table 2 Experimental results
[0082] Experimental Group Compressive strength(Mpa) Appearance A1 32.16 better A2 35.32 better A3 37.83 There are fine cracks A4 41.22 There are fine cracks A5 26.36 More cracks A6 — Rapid setting cannot be formed A7 — Rapid setting cannot be formed
[0083] The experimental results show that when slag and fly ash are mixed in a ratio of 5:5 (A4), the compressive strength is the highest, but cracking will occur. When slag and fly ash are mixed in a ratio of 3:7 (A2), the surface of the resulting marine engineering material is intact and has good physical properties.
[0084] Comparative Example 2 explores different Geopolymer fluid modulus and alkalinity Impact on the strength of marine engineering materials
[0085] A method for preparing marine engineering materials based on geopolymerization technology is different from Example 1 in that in the step of preparing the geopolymerizing agent, the masses of slag and fly ash are different, and they are directly mixed without grinding and activation. In the step of preparing the geopolymerizing liquid, the modulus or basicity of the obtained geopolymerizing liquid is different, as shown in the following table:
[0086] Table 6 Effect of different modulus and basicity on strength
[0087]
[0088]
[0089] The experimental results show that when the modulus of the geopolymer fluid is 1, different ratios of sodium hydroxide and sodium silicate result in different alkalinities. As the alkalinity of the geopolymer fluid increases, the strength of the marine engineering materials increases first and then decreases. The marine engineering materials obtained when the alkalinity is 6%-8% have relatively excellent strength, and the strength of the marine engineering materials is optimal when the alkalinity is 6%. When the modulus of the geopolymeric fluid is 1.2 or 1.4, the change law of the compressive strength of the marine engineering material is similar to that when the modulus of the geopolymeric fluid is 1, but the strength is lower than the strength of the marine engineering material when the modulus of the geopolymeric fluid is 1 and the alkalinity is 6%. Therefore, when the slag and fly ash are mixed in a weight ratio of 3:7 and the modulus of the geopolymeric fluid is 1, the strength of the marine engineering material is better when the alkalinity is 6%-8%, and the strength of the marine engineering material is optimal when the alkalinity is 6%; when the modulus of the geopolymeric fluid is 1.2, the strength of the marine engineering material is better when the alkalinity is 7%-8%, and when the modulus of the geopolymeric fluid is 1.4, the strength of the marine engineering material is better when the alkalinity is 8%.
[0090] Comparative Example 3: Influence of geopolymer grinding and activation on the strength of marine engineering materials
[0091] Based on the preparation method of the marine engineering materials of Group 4 in Comparative Example 2, two groups of experiments with different activation and non-activation were set according to the following table to prepare two marine engineering materials, and then the compressive strength of the obtained two marine engineering materials was tested. The results are as follows:
[0092] Table 7 Effect of activated geopolymer on strength of marine engineering materials
[0093]
[0094] Slag and fly ash are mixed and ground in a ball mill. Under the action of mechanical force, a large number of hollow glass beads in fly ash are destroyed, which stimulates its potential volcanic ash activity and enhances the activity of silicon and aluminum components, increasing the silicon and aluminum components participating in the geopolymerization reaction, which is conducive to making the material react more fully. Figure 5 As shown in the SEM image, it can be seen that the activated glass beads are destroyed and the specific surface area is increased. The dissolution and polymerization of silicon and aluminum components can be enhanced under the action of the geopolymeric fluid. The activated geopolymeric agent significantly improves the compressive strength of marine engineering materials.
[0095] Comparative Example 4: Influence of different cement ratios, sand ratios, and water-cement ratios on the strength of marine engineering materials
[0096] Based on the preparation method of the marine engineering materials of Group 4 in Comparative Example 2, multiple groups of experiments with different bone-cement ratios, sand ratios, and water-cement ratios were set according to the following table to prepare a variety of marine engineering materials, and then the compressive strength of the obtained marine engineering materials was tested. The results are as follows:
[0097] Table 8 Effects of different bone-cement ratios, sand ratios, and water-cement ratios on strength
[0098] The experimental results show that when the bone-cement ratio is 4:1, the sand ratio is 35%, and the water-cement ratio is 0.35, the marine engineering material has higher compressive strength.
[0099] Comparative Example 5: Influence of different contents of basalt fiber on the strength of marine engineering materials
[0100] Based on the preparation method of the marine engineering materials of Group 4 in Comparative Example 2, multiple groups of experiments were set up according to the following table: different contents of basalt fiber were added to the marine engineering material preparation step to prepare a variety of marine engineering materials, and then the compressive strength of the obtained marine engineering materials was tested. The results are as follows:
[0101] Table 9 Effect of different basalt fiber contents on the strength of marine engineering materials
[0102]
[0103]
[0104] The experimental results show that the compressive strength of the marine engineering materials is not significantly improved by adding basalt fiber. Further testing of the flexural strength of the marine engineering materials found that the addition of basalt fiber increased the flexural strength by 36%, which can improve the tolerance to ocean current impact, and the best effect is achieved when the addition of basalt fiber is 1%.
[0105] It is to be understood that the present invention is described by some embodiments, and it is known to those skilled in the art that various changes or equivalent substitutions may be made to these features and embodiments without departing from the spirit and scope of the present invention. In addition, under the teachings of the present invention, these features and embodiments may be modified to adapt to specific circumstances and materials without departing from the spirit and scope of the present invention. Therefore, the present invention is not limited by the specific embodiments disclosed herein, and all embodiments falling within the scope of the claims of this application are within the scope of protection of the present invention.
Claims
1. A method for preparing marine engineering materials based on geopolymerization technology, characterized in that: The steps include: Preparation of geopolymerization agent: grinding and activating slag and fly ash to obtain geopolymerization agent, wherein the mass ratio of slag to fly ash is 1:2-4; Preparation of geopolymer solution: after mixing sodium silicate solution and sodium hydroxide solution, adding solvent and mixing, to obtain geopolymer solution; Preparation of marine engineering materials: Mix the geopolymer and aggregate, then add a mixture of geopolymer liquid and water, stir evenly, pour into a mold, vibrate and compact, cure and demould, and obtain the marine engineering materials.
2. The preparation method according to claim 1, characterized in that The modulus of the geopolymer liquid is 1.0-1.4; the basicity of the geopolymer liquid is 6%-8%; Preferably, the modulus of the geopolymeric liquid is 1.2-1.4; the alkalinity of the geopolymeric liquid is 6%-7%.
3. The preparation method according to claim 1, characterized in that: The aggregate includes coarse aggregate and fine aggregate; Preferably, the coarse aggregate is at least one of pebbles and crushed stones, and the fine aggregate is sand; Preferably, the weight ratio of the coarse aggregate to the fine aggregate is 25%-40%; Preferably, the weight ratio of the coarse aggregate to the fine aggregate is 30%-35%.
4. The preparation method according to claim 1, characterized in that: The specific surface area of the geopolymer is greater than 400 m 2 / kg.
5. The preparation method according to claim 1, characterized in that: The mass ratio of the aggregate to the geopolymer is 2-5:1; Preferably, the mass ratio of the aggregate to the geopolymer is 3-5:
1.
6. The preparation method according to claim 1, characterized in that: In the step of preparing the marine engineering material, the mass ratio of water to geopolymerizing agent is 0.3-0.45; Preferably, the mass ratio of water to geopolymerizing agent is 0.35-0.
4.
7. The preparation method according to claim 1, characterized in that: The solvent includes at least one of purified water, distilled water, tap water, recycled water, groundwater, seawater, and waste alkali liquid intermediate; Preferably, the waste alkali solution intermediate is obtained by filtering, evaporating and adjusting the alkalinity of the waste alkali solution in sequence.
8. The preparation method according to any one of claims 1 to 7, characterized in that: The preparation of the marine engineering material also includes adding basalt fiber and mixing, and then pouring it into a mold and vibrating it to make it dense; Preferably, the amount of basalt fiber added is 0.3%-1.5% of the marine engineering material; Preferably, the basalt fiber is added in an amount of 0.5%-1.5% of the marine engineering material.
9. A marine engineering material obtained by the preparation method according to any one of claims 1 to 8, characterized in that: The compressive strength of the marine engineering material is 45-50MPa; Preferably, the compressive strength of the marine engineering material is 47Mpa.
10. A marine engineering material according to claim 9, characterized in that: The invention comprises the following components in parts by weight: 240-400 parts of geopolymerizing agent, 1000-1400 parts of aggregate, 140-160 parts of geopolymerizing liquid, and 50-100 parts of water; Preferably, the aggregate comprises 750-800 parts of coarse aggregate and 400-450 parts of fine aggregate; Preferably, the geopolymerizing agent comprises the following components in parts by weight: 85-95 parts of slag, 205-215 parts of fly ash, Preferably, the geopolymeric liquid comprises the following components in parts by weight: 60-65 parts of sodium silicate, 15-20 parts of sodium hydroxide, and 65-70 parts of solvent.
Citation Information
Patent Citations
A marine construction polymer material and its preparation method
CN115557739B